1994
DOI: 10.2166/wst.1994.0396
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of floc formation in sludge conditioning with polymers

Abstract: In flocculation of dilute suspensions a period of slow mixing is necessary to increase the probability of particle collisions that are necessary for flocculation to occur. When flocculating sludges, the collision frequency is so high that flocs are formed immediately after rapid mixing. However, controlled mixing of the flocculated sludge for some time period does improve dewaterability. The mechanisms that are involved have been studied in detail and the subject of this paper. The results show that after rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…2 and Table 1). This result agrees with that reported by Langer et al [12] and Wen et al [13] and differs from the data reported by Wu et al [14] and Chu and Lee [15] who demonstrated a continuous increase of floc size with polymer dosage. The discrepancy may be attributed to the different polymer features, such as charge type and molecular weight, used by different investigators as suggested by Lee and Liu [16].…”
Section: Discussionsupporting
confidence: 90%
“…2 and Table 1). This result agrees with that reported by Langer et al [12] and Wen et al [13] and differs from the data reported by Wu et al [14] and Chu and Lee [15] who demonstrated a continuous increase of floc size with polymer dosage. The discrepancy may be attributed to the different polymer features, such as charge type and molecular weight, used by different investigators as suggested by Lee and Liu [16].…”
Section: Discussionsupporting
confidence: 90%
“…The van der Waals force could also be important in the adsorption reaction owing to the high molecular weight of polyelectrolyte and less negative value of ZP (−7.1 mV) on sludge surfaces. The adsorbed polyelectrolyte formed loops, trains, and tails on sludge surfaces [22,23]. Due to hindrance and electrostatic repulsion, it was difficult for the polyelectrolyte to adsorb on the loops, tails, or the surface of the particles at higher concentration.…”
Section: Zeta Potentialmentioning
confidence: 99%
“…According to Christensen and coworkers (1993) the unreliability of the CST may be ascribed to the increased viscosity of the liquid phase when polymer overdosing is applied. At these high dosages, breakage of flocs by stirring leads to further consumption of polymer in solution (Langer et al, 1994), reducing its viscosity and yielding a lower CST value at longer shearing times.…”
Section: Sheared Cstmentioning
confidence: 99%